2020
DOI: 10.1111/ina.12746
|View full text |Cite
|
Sign up to set email alerts
|

The effects of carbon dioxide exposure concentrations on human vigilance and sentiment in an enclosed workplace environment

Abstract: In this study, fifteen participants were exposed to different carbon dioxide (CO2) concentrations in an enclosed environmental chamber to investigate the potential effects of elevated CO2 concentrations on human vigilance and sentiment. The psychomotor vigilance test (PVT), the Karolinska Sleepiness Scale (KSS), and the Positive and Negative Affect Schedule (PANAS) were measured before and after each 4‐hour CO2 exposure session. The statistical analyses of the PVT performance metrics showed that the human vigi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
3
10
0
1
Order By: Relevance
“…In the present study, a statistically significant difference was observed in the main effect of time but not CO 2 conditions in the classical repeated ANOVA consistent with two recent studies, 27,38 indicating that daytime sleepiness developed even under control normocapnic conditions. A previous study found that CO 2 at around 3000 ppm resulted in changes in heart rate variability with increased sleepiness 16 .…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, a statistically significant difference was observed in the main effect of time but not CO 2 conditions in the classical repeated ANOVA consistent with two recent studies, 27,38 indicating that daytime sleepiness developed even under control normocapnic conditions. A previous study found that CO 2 at around 3000 ppm resulted in changes in heart rate variability with increased sleepiness 16 .…”
Section: Discussionsupporting
confidence: 93%
“…Especially the self-reported highest sleepiness in the fully occupied Max. CO 2 condition that is in line with previous research (e.g., Vehviläinen et al, 2016 ; Zhang et al, 2017 ), although not found by others (e.g., Pang et al, 2021 ), is intriguing as objectively measured cardiovascular recovery time is the lowest in this condition. It underpins the stress assumption of feeling exhausted without being able to relax on a physiological level.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our results indicated that attention, risky decision-making, and executive ability were significantly impaired as the CO 2 concentration increased from 1500 to 5000 ppm. Similarly, a significant detrimental effect of CO 2 exposure on vigilance was also found at concentrations as low as 3500 ppm using the psychomotor vigilance test (PVT) in our previous study [35]. Snow et al [13] stated that the increase in CO 2 concentration from 800 to 2700 ppm could lead to reduced cognitive flexibility and executive ability, given lack of learning effect, as examined by the shifting attention test and the Stroop test.…”
Section: Comparison With Previous Studiessupporting
confidence: 51%